Transcriptome Identified lncRNAs Associated with Renal Fibrosis in UUO Rat Model - Sun, Jiazeng; Zhang, Shang; Shi, Bianhua; Zheng, Dexian; Shi, Juan (Frontiers in Physiology, 2017)
Renal fibrosis represents a final common outcome of many renal diseases and has attracted a great deal of attention. To better understand whether lncRNAs could be a player in this process or be a biomarker for renal fibrosis diagnosis, we compared transcriptome sequencing data on renal tissues and urine respectively between UUO (unilateral ureteral obstruction) and shamed (Sham) rat model. Numerous genes including lncRNAs with significant changes in their expression were identified. 24 lncRNAs were up-regulated and 79 lncRNAs were down-regulated in the renal tissues of the UUO rats. 625 lncRNAs were up-regulated and 177 lncRNAs were down-regulated in urines of the UUO rats. Among the lncRNAs upregulated in renal tissue of UUO rats, 19 lncRNAs were predicted containing several conserved Smad3 binding motifs in the promoter. Among them, lncRNAs with putative promoter containing more than 4 conserved Smad3 binding motifs were demonstrated to be induced by TGF-β significantly in normal rat renal tubular epithelial NRK-52E cells. We further confirmed that lncRNA TCONS_00088786 and TCONS_01496394 were regulated by TGF-β stimulation and also can influence the expression of some fibrosis-related genes through a feedback loop. Based on transcriptome sequencing data, bioinformatics analysis and qRT-PCR detection, we also demonstrated lncRNA in urine are detectable and might be a novel biomarker of renal fibrosis. These results provide new information for the involvement of lncRNAs in renal fibrosis, indicating that they may serve as candidate biomarkers or therapeutic targets in the future.